Medium-gradient resistor disc for lightning arrester monitor and preparation method of medium-gradient resistor disc

By using zinc oxide, functionalized graphene and platinum nanoparticles in the lightning arrester monitor, an efficient conductive network is formed, which solves the problems of high residual lightning waves and low charge transfer performance of the medium gradient resistor sheet, and realizes the power system stable operation and miniaturized installation of monitors.

CN119230224APending Publication Date: 2024-12-31NANYANG JINGUAN ELECTRIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411447111.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The problems of high residual voltage of lightning waves and low charge transfer performance for existing lightning arrester monitors affect the stable operation of the power system.

Method used

Using zinc oxide, functionalized graphene and platinum nanoparticles as main components, by adjusting the mass ratio of graphene and platinum nanoparticles, combining special low-temperature glass and bismuth-based low-temperature lead-free glass glaze powder, a high-efficiency conductive network is formed and the resistance is reduced. The residual voltage of the lightning wave of the sheet improves the charge transfer performance.

Benefits of technology

It realizes a medium-gradient resistor sheet with low residual voltage of lightning wave and high charge transfer performance, which can meet the requirements of high charge transfer testing, promotes the safe and stable operation of the power system, and reduces production difficulty and cost through miniaturization and convenient installation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of resistor discs, and provides a medium-gradient resistor disc for a lightning arrester monitor and a preparation method thereof.The medium-gradient resistor disc for the lightning arrester monitor is prepared from, by weight, 90-95 parts of zinc oxide, 3-5 parts of an additive and 1-3 parts of a sintering accelerant; the additive comprises functionalized graphene and platinum nanoparticles, and the mass ratio of the functionalized graphene to the platinum nanoparticles is (1: 20)-(20: 1). According to the technical scheme, the problems of high lightning wave residual voltage and low charge transfer performance of the medium-gradient resistor disc for the lightning arrester monitor in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resistor sheets, and in particular to a medium-gradient resistor sheet for a lightning arrester monitor and a preparation method thereof. Background Art

[0002] Lightning arresters are important protective devices for ensuring the safe operation of electrical equipment in power systems. They can effectively limit the damage to equipment caused by lightning overvoltage and operating overvoltage. Lightning arrester monitors are key devices used to monitor the operating status of lightning arresters in real time. By monitoring parameters such as lightning arrester leakage current, they can promptly detect performance changes and potential faults of lightning arresters to ensure stable and reliable operation of power systems. As the core component of lightning arrester monitors, the performance of resistors directly determines the accuracy and reliability of the monitors.

[0003] A medium gradient resistor is an electronic component with specific resistance characteristics. Its resistance characteristics show that within a certain voltage range, the resistance value changes relatively smoothly with the change of voltage, and in terms of microstructure, the distribution of the internal resistor material has a moderate gradient characteristic. This gradient characteristic enables the resistor to evenly withstand the electric field stress during operation, avoiding premature damage caused by local electric field concentration, thereby improving the overall performance and service life of the resistor. However, under different working conditions, the charge transfer performance of some resistors may fluctuate, causing the charge transfer ability of the resistor to change, which in turn affects the lightning arrester monitor's accurate judgment of the working status of the lightning arrester. In addition, in strong lightning weather, higher lightning wave residual pressure may cause power equipment to malfunction, affecting the stable operation of the power system. Therefore, the development of a medium gradient resistor with low lightning wave residual pressure and high charge transfer performance for a lightning arrester monitor has important practical significance and technical value. Summary of the invention

[0004] The present invention provides a medium-gradient resistor for a lightning arrester monitor and a preparation method thereof, which solves the problems of high residual voltage of lightning waves and low charge transfer performance of medium-gradient resistors for lightning arrester monitors in the related art.

[0005] The technical solution of the present invention is as follows: The present invention provides a medium gradient resistor for a lightning arrester monitor, comprising the following component raw materials in parts by weight: 90-95 parts of zinc oxide, 3-5 parts of additives, and 1-3 parts of sintering accelerators; The additive comprises functionalized graphene and platinum nanoparticles, and the mass ratio of the functionalized graphene to the platinum nanoparticles is 1:20 to 20:1.

[0006] As a further technical solution, the mass ratio of the functionalized graphene to the platinum nanoparticles is 10:1-2.

[0007] As a further technical solution, the particle size of the platinum nanoparticles is 10-30 nm.

[0008] As a further technical solution, the functionalized graphene consists of sulfur-doped graphene and nitrogen-doped graphene, and the mass ratio of the sulfur-doped graphene to the nitrogen-doped graphene is 2-3:1.

[0009] As a further technical solution, the sulfur doping rate of the sulfur-doped graphene is 10wt%~30wt%, and the nitrogen doping rate of the nitrogen-doped graphene is 5wt%~15wt%.

[0010] In the present invention, sulfur-doped graphene and nitrogen-doped graphene are added as functionalized graphene materials, and their synergistic effect is fully exerted by adjusting their mass ratio, thereby reducing the lightning wave residual voltage of the resistor and improving the charge transfer performance of the resistor.

[0011] As a further technical solution, the sintering accelerator is composed of special low-temperature glass, boric acid, and titanium dioxide, and the mass ratio of the special low-temperature glass, the boric acid, and the titanium dioxide is 3:1:1.

[0012] As a further technical solution, the following component raw materials are also included in weight: 1 to 4 parts of flux, wherein the flux includes one or more of oxalic acid, acetic acid, citric acid, malic acid, and tartaric acid.

[0013] As a further technical solution, the following component raw materials are also included in parts by weight: 2 to 6 parts of a uniformity aid, wherein the uniformity aid includes one or more of zinc hydroxide, cobalt hydroxide, nickel hydroxide, aluminum hydroxide, and magnesium hydroxide.

[0014] As a further technical solution, it also includes the following component raw materials in parts by weight: 7 to 10 parts of bismuth-based low-temperature lead-free glass glaze powder, which is composed of the following raw materials in parts by weight: 4.5 to 5 parts of bismuth oxide, 0.5 to 1 part of silicon dioxide, 0.5 to 0.8 parts of boron trioxide, 0.3 to 0.5 parts of aluminum oxide, 0.6 to 0.8 parts of calcium oxide, 0.5 to 1 part of lithium oxide, and 0.5 to 0.8 parts of potassium oxide.

[0015] As a further technical solution, the preparation method of the bismuth-based low-temperature lead-free glass glaze powder includes the following steps: mixing the raw materials of the bismuth-based low-temperature lead-free glass glaze powder, melting, cooling, and crushing to obtain the bismuth-based low-temperature lead-free glass glaze powder.

[0016] The present invention also provides a method for preparing a medium gradient resistor for a lightning arrester monitor, comprising the following steps: S1, weighing the raw materials of the resistor, mixing, granulating and molding to obtain a resistor green body; S2, drying, calcining and debinding the resistor green body to obtain a resistor pre-sintered green body; S3, spraying aluminum on the end surface of the pre-sintered body of the resistor, coating the side with bismuth-based low-temperature lead-free glass glaze, and obtaining a medium-gradient resistor after sintering.

[0017] As a further technical solution, the debinding temperature is 300-400°C, the debinding time is 1-3 hours, and the sintering temperature is 1200-1300°C.

[0018] The working principle and beneficial effects of the present invention are: In the present invention, functionalized graphene and platinum nanoparticles are added as additives to reduce the local current density of the resistor, reduce the voltage across the resistor, and improve the charge transfer speed and efficiency of the resistor. By limiting the proportional relationship between the two, the functionalized graphene and platinum nanoparticles can play a synergistic role to form an efficient conductive network, reduce the lightning wave residual pressure of the resistor, improve the charge transfer performance of the resistor, and protect the safe and stable operation of the power system. A single resistor with a diameter of 52mm can withstand the 2ms square wave repetitive charge transfer test of Qrs 5C, which can meet the 2ms charge transfer test requirements of all lightning arrester monitors; for relatively low requirements, a resistor with a diameter of 20mm can meet the 2ms repetitive charge transfer requirements. The significant reduction in the diameter of the resistor is conducive to the miniaturization of the monitor and the convenience of installation. In the monitor for high-voltage lightning arresters, the finished resistor is about 5mm thick and the reference voltage is about 500V at 1mA DC. For the monitor of the lowest level lightning arrester, the finished resistor is about 2mm thick and 20mm in diameter. In this case, it is easy to use dry pressing and non-grinding processes to achieve production, reducing production difficulty and cost. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] In the following examples and comparative examples: Sulfur-doped graphene: sulfur doping rate is 10wt%~30wt%, the manufacturer is Xi'an Qiyue Biotechnology Co., Ltd.; Nitrogen-doped graphene: nitrogen doping rate 5wt%~15wt%, particle size 1.2~4.8μm, specific surface area 100~300m 2 / g, the manufacturer is Shandong Jincheng Graphene Technology Co., Ltd.; Platinum nanoparticles: particle size 10nm, manufacturer is Zhongke Leiming (Beijing) Technology Co., Ltd.; Special low temperature glass: bulk density is 0.57g / cm 3 , Model D270, melting point 700℃, linear expansion coefficient 90×10 -7 , the manufacturer is Anmi Micro-Nano New Materials Co., Ltd.

[0021] Example 1 Bismuth-based low-temperature lead-free glass glaze powder: weigh 4.5 parts of bismuth oxide, 0.5 parts of silicon dioxide, 0.5 parts of boron trioxide, 0.3 parts of aluminum oxide, 0.6 parts of calcium oxide, 0.5 parts of lithium oxide, and 0.5 parts of potassium oxide, mix them evenly, melt them at 800°C, pour them into water and cool them quickly to form glass slag, and obtain bismuth-based low-temperature lead-free glass glaze powder with a particle size D50 of 1 μm after ball milling and screening.

[0022] A method for preparing a medium gradient resistor for a lightning arrester monitor comprises the following steps: S1, weighing 90 parts of zinc oxide, 3 parts of additives, 0.6 parts of special low-temperature glass, 0.2 parts of boric acid, 0.2 parts of titanium dioxide, 1 part of oxalic acid, and 2 parts of zinc hydroxide, mixing, drying, granulating, and molding to obtain a resistor green body, wherein the additives include functionalized graphene and platinum nanoparticles in a mass ratio of 15:1, and the functionalized graphene is sulfur-doped graphene; S2. After the resistor green body is dried, it is placed in a calcination and debinding chamber, and the temperature is raised to 300°C at a heating rate of 3°C / min. The calcination and debinding are started and the temperature is kept for 3 hours. The green body is cooled to room temperature to obtain a resistor pre-sintered body. S3. Use an automatic aluminum spraying machine to fully spray the end face of the pre-sintered resistor body with electrodes, coat the side with bismuth-based low-temperature lead-free glass glaze, and sinter at 1200°C for 30 minutes to obtain a medium-gradient resistor with a gradient of 100V / mm.

[0023] Example 2 Bismuth-based low-temperature lead-free glass glaze powder: weigh 4.8 parts of bismuth oxide, 0.8 parts of silicon dioxide, 0.6 parts of boron trioxide, 0.4 parts of aluminum oxide, 0.7 parts of calcium oxide, 0.8 parts of lithium oxide, and 0.6 parts of potassium oxide, mix them evenly and melt them at 850°C, pour them into water and quickly cool them to form glass slag, and then obtain bismuth-based low-temperature lead-free glass glaze powder with a particle size D50 of 2μm after ball milling and screening.

[0024] A method for preparing a medium gradient resistor for a lightning arrester monitor comprises the following steps: S1, weighing 92 parts of zinc oxide, 4 parts of additives, 1.2 parts of special low-temperature glass, 0.4 parts of boric acid, 0.4 parts of titanium dioxide, 3 parts of acetic acid, and 4 parts of cobalt hydroxide, mixing, drying, granulating, and molding to obtain a resistor green body, wherein the additives include functionalized graphene and platinum nanoparticles in a mass ratio of 15:1, and the functionalized graphene is sulfur-doped graphene; S2. After the resistor green body is dried, it is placed in a calcination and debinding chamber, and the temperature is raised to 350°C at a heating rate of 4°C / min. The calcination and debinding are started, and the temperature is kept for 2 hours. The resistor green body is cooled to room temperature to obtain a resistor pre-sintered body. S3. Use an automatic aluminum spraying machine to fully spray the end face of the pre-sintered resistor body with electrodes, coat the side with bismuth-based low-temperature lead-free glass glaze, and sinter at 1250°C for 20 minutes to obtain a medium-gradient resistor with a gradient of 100V / mm.

[0025] Example 3 Bismuth-based low-temperature lead-free glass glaze powder: weigh 5 parts of bismuth oxide, 1 part of silicon dioxide, 0.8 parts of boron trioxide, 0.5 parts of aluminum oxide, 0.8 parts of calcium oxide, 1 part of lithium oxide, and 0.8 parts of potassium oxide, mix them evenly, melt them at 900°C, pour them into water and quickly cool them to form glass slag, and obtain bismuth-based low-temperature lead-free glass glaze powder with a particle size D50 of 3μm after ball milling and screening.

[0026] A method for preparing a medium gradient resistor for a lightning arrester monitor comprises the following steps: S1, weighing 95 parts of zinc oxide, 5 parts of additives, 1.8 parts of special low-temperature glass, 0.6 parts of boric acid, 0.6 parts of titanium dioxide, 4 parts of citric acid, and 6 parts of nickel hydroxide, mixing, drying, granulating, and molding to obtain a resistor green body, wherein the additives include functionalized graphene and platinum nanoparticles in a mass ratio of 15:1, and the functionalized graphene is sulfur-doped graphene; S2. After the resistor green body is dried, it is placed in a calcination and debinding chamber, and the temperature is raised to 400°C at a heating rate of 5°C / min. The calcination and debinding are started and the temperature is kept for 1 hour. The resistor green body is cooled to room temperature to obtain a resistor pre-sintered body. S3. Use an automatic aluminum spraying machine to fully spray the end face of the pre-sintered resistor body with electrodes, coat the side with bismuth-based low-temperature lead-free glass glaze, and sinter at 1300°C for 10 minutes to obtain a medium-gradient resistor with a gradient of 100V / mm.

[0027] Example 4 Compared with Example 1, the difference of Example 4 is that the mass ratio of the functionalized graphene and the platinum nanoparticles in the additive is 10:1, wherein the functionalized graphene is sulfur-doped graphene.

[0028] Example 5 Compared with Example 1, the difference of Example 5 is that the mass ratio of the functionalized graphene and the platinum nanoparticles in the additive is 10:2, wherein the functionalized graphene is sulfur-doped graphene.

[0029] Example 6 Compared with Example 1, the difference of Example 6 is that the mass ratio of the functionalized graphene and the platinum nanoparticles in the additive is 10:3, wherein the functionalized graphene is sulfur-doped graphene.

[0030] Example 7 Compared with Example 5, the difference in Example 7 is that the functionalized graphene is nitrogen-doped graphene.

[0031] Example 8 Compared with Example 5, the difference of Example 8 is that the functionalized graphene consists of sulfur-doped graphene and nitrogen-doped graphene in a mass ratio of 1:1.

[0032] Example 9 Compared with Example 5, the difference of Example 9 is that the functionalized graphene consists of sulfur-doped graphene and nitrogen-doped graphene in a mass ratio of 2:1.

[0033] Example 10 Compared with Example 5, the difference of Example 10 is that the functionalized graphene consists of sulfur-doped graphene and nitrogen-doped graphene in a mass ratio of 3:1.

[0034] Embodiment 11 Compared with Example 5, the difference of Example 11 is that the functionalized graphene consists of sulfur-doped graphene and nitrogen-doped graphene in a mass ratio of 4:1.

[0035] Comparative Example 1 Compared with Example 1, Comparative Example 1 is different in that no additive is added.

[0036] Comparative Example 2 Compared with Example 1, the difference in Comparative Example 2 is that the additive is only functionalized graphene.

[0037] Comparative Example 3 Compared with Example 1, Comparative Example 3 is different in that the additive is only platinum nanoparticles.

[0038] The medium gradient resistor for a lightning arrester monitor prepared in Examples 1 to 11 and Comparative Examples 1 to 3 was tested according to the following method: 1. Residual voltage: According to the test method specified in JB / T 10492-2011 "Detection device for metal oxide arresters", the residual voltage of the test sample is tested. The test conditions are: single piece D52, 20kA.

[0039] 2. Charge transfer performance improvement rate: According to the test method for rated repetitive transfer charge specified in GB / T 11032-2020 "AC Gapless Metal Oxide Arrester", the charge transfer performance improvement rate of the test sample is tested. The test time is 2ms. The charge transfer performance improvement rate = [(charge transferred after improvement - charge transferred before improvement) / charge transferred before improvement] × 100%.

[0040] The test results are shown in the following table: Table 1 Performance test results of medium gradient resistors for lightning arrester detectors prepared in Examples 1 to 11 and Comparative Examples 1 to 3

[0041] Compared with Comparative Example 1, Example 1 adds additives, and the residual voltage of Example 1 is lower than that of Comparative Example 1, and the charge transfer performance improvement rate is higher than that of Comparative Example 1, indicating that adding additives can reduce the lightning wave residual voltage of the resistor and improve the charge transfer performance of the resistor. Compared with Example 1, Comparative Example 2 only adds functionalized graphene, and Comparative Example 3 only adds platinum nanoparticles. As a result, the residual voltage of Example 1 is lower than that of Comparative Examples 2 and 3, and the charge transfer performance improvement rate is higher than that of Comparative Examples 2 and 3, indicating that the functionalized graphene and platinum nanoparticles play a synergistic role, which can reduce the lightning wave residual voltage of the resistor and improve the charge transfer performance of the resistor. In Examples 1 and Examples 4 to 6, functionalized graphene and platinum nanoparticles in different mass ratios are added. As a result, the residual voltage of Examples 4 and 5 is lower than that of Examples 1 and 6, and the charge transfer performance improvement rate is higher than that of Examples 1 and 6, indicating that when the mass ratio of functionalized graphene and platinum nanoparticles is 10:1~2, the lightning wave residual voltage of the resistor obtained is lower and the charge transfer performance of the resistor is higher.

[0042] Compared with Examples 5 and 7, Examples 8 to 11 simultaneously add sulfur-doped graphene and nitrogen-doped graphene. As a result, the residual voltage of Examples 8 to 11 is lower than that of Examples 5 and 7, and the charge transfer performance improvement rate is higher than that of Examples 5 and 7, indicating that sulfur-doped graphene and nitrogen-doped graphene play a synergistic role, which can reduce the lightning wave residual voltage of the resistor and improve the charge transfer performance of the resistor. Sulfur-doped graphene and nitrogen-doped graphene in different mass ratios are added to Examples 8 to 11. As a result, the residual voltage of Examples 9 and 10 is lower than that of Examples 8 and 11, and the charge transfer performance improvement rate is higher than that of Examples 8 and 11, indicating that when the mass ratio of sulfur-doped graphene to nitrogen-doped graphene is 2 to 3:1, the lightning wave residual voltage of the resistor obtained is lower and the charge transfer performance of the resistor is higher.

[0043] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A medium gradient resistor for a lightning arrester monitor, characterized in that: The invention comprises the following raw materials in parts by weight: 90-95 parts of zinc oxide, 3-5 parts of additives, and 1-3 parts of sintering accelerators; the additives comprise functionalized graphene and platinum nanoparticles, and the mass ratio of the functionalized graphene to the platinum nanoparticles is 1:20-20:

1.

2. The medium gradient resistor for a lightning arrester monitor according to claim 1, characterized in that: The mass ratio of the functionalized graphene to the platinum nanoparticles is 10:1-2.

3. The medium gradient resistor for a lightning arrester monitor according to claim 1, characterized in that: The particle size of the platinum nanoparticles is 10-30 nm.

4. The medium gradient resistor for a lightning arrester monitor according to claim 1, characterized in that: The functionalized graphene consists of sulfur-doped graphene and nitrogen-doped graphene, and the mass ratio of the sulfur-doped graphene to the nitrogen-doped graphene is 2-3:

1.

5. The medium gradient resistor for a lightning arrester monitor according to claim 4, characterized in that: The sulfur doping rate of the sulfur-doped graphene is 10wt%-30wt%, and the nitrogen doping rate of the nitrogen-doped graphene is 5wt%-15wt%.

6. The medium gradient resistor for a lightning arrester monitor according to claim 1, characterized in that: The sintering accelerator is composed of special low-temperature glass, boric acid and titanium dioxide, and the mass ratio of the special low-temperature glass, the boric acid and the titanium dioxide is 3:1:

1.

7. The medium gradient resistor for a lightning arrester monitor according to claim 1, characterized in that: The invention also includes the following raw materials in parts by weight: 1 to 4 parts of flux, wherein the flux includes one or more of oxalic acid, acetic acid, citric acid, malic acid and tartaric acid.

8. The medium gradient resistor for a lightning arrester monitor according to claim 1, characterized in that: The invention also includes the following raw materials in parts by weight: 2 to 6 parts of a uniformity aid, wherein the uniformity aid includes one or more of zinc hydroxide, cobalt hydroxide, nickel hydroxide, aluminum hydroxide, and magnesium hydroxide.

9. The medium gradient resistor for a lightning arrester monitor according to claim 1, characterized in that: It also includes the following component raw materials in parts by weight: 7 to 10 parts of bismuth-based low-temperature lead-free glass glaze powder, which is composed of the following raw materials in parts by weight: 4.5 to 5 parts of bismuth oxide, 0.5 to 1 part of silicon dioxide, 0.5 to 0.8 parts of boron trioxide, 0.3 to 0.5 parts of aluminum oxide, 0.6 to 0.8 parts of calcium oxide, 0.5 to 1 part of lithium oxide, and 0.5 to 0.8 parts of potassium oxide.

10. The method for preparing a medium gradient resistor for a lightning arrester monitor according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, weighing the raw materials of the resistor, mixing, granulating and molding to obtain a resistor green body; S2, drying, calcining and debinding the resistor green body to obtain a resistor pre-sintered green body; S3, spraying aluminum on the end surface of the pre-sintered body of the resistor, coating the side with bismuth-based low-temperature lead-free glass glaze, and obtaining a medium-gradient resistor after sintering.